Technological Innovation in School Management: A Challenge and Opportunity - Agustina, Gina; Ulfatin, Nurul; Sunandar, Asep (Proceedings Series of Educational Studies, 2024)
This research aims to examine the impact of technological innovation on school management, especially in terms of efficiency, effectiveness and service quality. Through a literature review, this research analyzes various studies that discuss the application of information technology in educational management. The results of the analysis show that technological innovation has great potential to increase operational efficiency, facilitate collaboration, and improve the quality of educational services. However, this research also identified a number of challenges such as the digital divide, data security and lack of human resource competence. This research concludes that despite challenges, technological innovation is the key to improving the quality of education in the digital era. To achieve this, careful planning, cross-sector collaboration and human resource capacity development are needed.